Examining the legend and music of Australian saxophonist, Frank Smith - Whiteoak, Ralph (Jazz Research Journal, 2015)
Like most countries that possess a history of jazz performance, Australia has its share of legendary jazz figures. Of these, the saxophonist Frank Smith (1927–1974) is considered to have been the most talented and original modern jazz saxophonist of his generation. This article questions aspects of the Smith ‘legend’ by testing various claims, anecdotes and stories against data provided by those who were close to him, against other data extracted from an examination of primary printed sources of his era, and also by examining claimed influences on Smith’s creativity. The article seeks to explain what it was about Smith’s approach to playing jazz that gave him such a reputation for originality and virtuosity. Smith’s place in the pantheon of pioneer modernists in Australian jazz is based on a considerable, diverse and often anecdotal range of recollected strengths and idiosyncrasies. These range from strictly musical qualities, including his extraordinary ear, virtuosic execution, harmonic innovativeness and mentoring generosity, to more personal characteristics, including his notoriously dishevelled and mistreated saxophone. It is impossible to span the full spectrum of the Smith legend here so, while I encompass some of its features, my primary analytical musical focus is upon the aspect of his musicianship for which there is hard documentary evidence in the form of unpublished sound recordings. In particular, it considers what credence can be given to claims that Smith’s strikingly original ‘sound’ was influenced by his interest in the theories of the composer Paul Hindemith.